SOCIAL PROBLEM OF YOUTH CRIME AND THE FORMATION OF THE LEGAL CULTURE OF STUDENTS - Abdurashidovna, Mukhitdinova Firyuza; Akhatovna, Akhmedshaeva Mavlyuda (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is determined by the fact that the novel "Crime and Punishment" and is considered by modern scholars as an introduction to the artistic world of the five major novels of the writer. It touches upon a complex set of cultural, historical, social, nationally psychological, moral and philosophical problems that are deeply developed in the subsequent work of Dostoevsky.